Finely Controlled Stepwise Engineering of Pore Environments and Mechanistic Elucidation of Water‐Stable, Flexible 2D Porous Coordination Polymers. Issue 24 (10th April 2018) - Wang, Haijun; Cao, Haifei; Zheng, Jia‐jia; Mathew, Simon; Hosono, Nobuhiko; Zhou, Bihang; Lyu, Hongliang; Kusaka, Shinpei; Jin, Wanqin; Kitagawa, Susumu; Duan, Jingui
Abstract: Two porous coordination polymers (PCPs) with different topologies (NTU‐19:sql and NTU‐20:dia ) underwent finely controlled, stepwise crystal conversions to yield a common water‐stable, flexible 2D framework (NTU‐22:kgm ). The crystal conversions occurred directly at higher temperature via the 3D intermediate (NTU‐21:nbo ), which could be observed at lower temperature. The successful isolation of the intermediate product of NTU‐21, characterization with in situ PXRD and UV/Vis spectra were combined with DFT calculations to allow an understanding of the dynamic processes at the atomic level. Remarkably, breakthrough experiments demonstrate NTU‐22 with integral structural properties allowed significant CO2 /CH4 mixture separation. Abstract : Crystal to crystal : Two porous coordination polymers (PCPs) with different topologies (sql anddia ) underwent crystal conversion to yield the first water‐stable, two‐dimensional and flexiblekgm PCP, via or not via a 3Dnbo intermediate. Plausible mechanisms for crystal conversions were elucidated at the atomic level both experimentally and theoretically (see figure).